2022
DOI: 10.1089/hum.2021.131
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of FX201, a Novel Intra-Articular IL-1Ra Gene Therapy for Osteoarthritis Treatment, in a Rat Model

Abstract: Osteoarthritis (OA) is a disabling, degenerative disease characterized by progressive cartilage and bone damage. There remains a need for local therapies that, following a single injection, can provide long-term pain relief and functional improvement and potentially delay disease progression. FX201 is a novel, intra-articular (IA), interleukin-1 receptor antagonist (IL-1Ra) gene therapy in development for the treatment of OA. In this study, we assessed the efficacy, biodistribution, and safety of helper-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In addition, authors observed a downregulation of pro-inflammatory cytokines (IL-6 and TNF-α) blocking the MIA-induced inflammatory cascade. Finally, Senter et al evaluated efficacy, biodistribution and safety of FX201 (HDAd expressing human IL-1Ra) and its ratIL-1Ra expressing ortholog vector in the rat ACLT OA model ( 20 ). IL-1Ra gene therapy significantly reduced joint damage in arthritic animals, and the gene therapy vectors were shown to be well-tolerated and to remain predominantly at the injection site after IA injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, authors observed a downregulation of pro-inflammatory cytokines (IL-6 and TNF-α) blocking the MIA-induced inflammatory cascade. Finally, Senter et al evaluated efficacy, biodistribution and safety of FX201 (HDAd expressing human IL-1Ra) and its ratIL-1Ra expressing ortholog vector in the rat ACLT OA model ( 20 ). IL-1Ra gene therapy significantly reduced joint damage in arthritic animals, and the gene therapy vectors were shown to be well-tolerated and to remain predominantly at the injection site after IA injection.…”
Section: Discussionmentioning
confidence: 99%
“…A Phase I, open-label study (NCT02790723) evaluating the safety of intra-articular injection of scAAV2.5IL-1Ra in nine subjects with moderate knee OA has recently been completed with encouraging results. A Phase I open-label, single ascending dose study (NCT04119687) assessing the safety and tolerability of FX201, the HDAd-IL-1Ra intra-articular gene therapy described by Senter et al, in 72 subjects with moderate to severe knee OA has been recently completed, and the sponsor reported “very compelling” results (no further details were given) ( 20 ). A post marketing surveillance study (NCT03412864) including 3,000 OA patients (Kellgren–Lawrence grade III) assessing adverse events as primary endpoints is currently underway for TG-C.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were assigned to one of the four treatment groups (Sham, OA, OA + Ad-NC, and OA + Ad-GCN2) using a randomized stratification scheme before the anterior cruciate ligament transection (ACLT) surgery. The anterior cruciate ligaments of the right knee joint (excluding rats in the Sham group) were transected as previously described 15 under 5% pentobarbital sodium anesthesia. Rats in the Sham group underwent surgery, but did not undergo ACLT.…”
Section: Methodsmentioning
confidence: 99%
“…The interleukin-1 receptor antagonist (IL-1Ra) has been the most studied reflecting the status of IL-1 as a popular, albeit controversial, therapeutic target for OA. The most recent publications in this context report safety and efficacy in mice [10], rats [11 ▪ ,12] and horses [8,10] using AAV and HC-adenovirus vectors. These data support two current phase I clinical trials, described in the next section.…”
Section: Preclinical Evaluation In Animal Models Of Osteoarthritismentioning
confidence: 99%